Climatological seasonal variation of the upper ocean salinity. (13th November 2021) - Liu, Yuanxin; Cheng, Lijing; Pan, Yuying; Abraham, John; Zhang, Bin; Zhu, Jiang; Song, Junqiang
Abstract: Salinity plays a vital role in regulating ocean density, stratification and circulation, and is an indicator of the coupling between the ocean, atmosphere and land through the water cycle. This study provides a spatially complete look of the seasonal variation of the upper 2, 000 m ocean salinity from regional to global scales, and assesses the robustness of the signals. The potential drivers of this variation are also investigated by comparing salinity changes with surface precipitation and evaporation. New observations show a robust seasonal variation in global ocean salinity from the surface down to 350 m depth that exceeds the observational uncertainty, and in some regions, the variation can be detected at 2, 000 m. Regions with a seasonal variation of sea surface salinity (SSS) larger than 0.6 g⋅kg −1 include the Northwest Pacific, Northwest Atlantic, tropical oceans and the northeast Indian Ocean. From 5°N to 30°N (20°N to 5°N), the sea surface is fresher (saltier) in the first half of the year and gets saltier (fresher) in the second half of the year, because of surface precipitation and evaporation changes associated with monsoons and the seasonal changes in atmospheric circulation. In the middle and high latitudes, the evaporation‐minus‐precipitation is mismatched with local salinity changes, suggesting that river runoff, sea ice change and ocean dynamics have a controlling role. On zonal average, the subsurface (50–160 m) generally shows salinity anomalies with an opposite sign to those of the near surface regions (0–50 m), indicating the importance of ocean dynamics. There are notable differences in global SSS variation between Argo‐only products and datasets that merge all observations, revealing the insufficiency of Argo network in shallow oceans and polar regions. To overcome this, an integrated ocean observational network is strongly recommended. Abstract : Seasonal variations of the zonal mean salinity changes from 0 to 1800 m at January and July.